Konsep Persediaan Minimum Maksimum Pengendalian Part Alat Berat Tambang PT Semen Padang - Dio Putera Hasian (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2012)
Bureau of mining heavy equipment maintenance at PT. Semen Padang have task in maintenance mine heavy equipment with preventive maintenance although breakdown maintenance. Part inventory is needed to make this activity work properly. If stockout happened will have the impact to PT.Semen Padang mining and production activity. To solve this problem, minimum-maximum inventory control policy is used to give an optimum value of inventory mine heavy equipment. This research is focused in filter and lubricant inventory because they have high demand rate. Data consumption filter and lubricant from January until December 2010 is used in this research. The service level that used is 95%. The result is quantity optimum inventory mine heavy equipment at filter and lubricant with application part inventory of mine heavy equipment. Because it can keep stockout although excess inventory.Keywords: stockout, optimum, inventory